Cultivo de pimenta biquinho sob lâminas de irrigação e doses de nitrogênio no cerrado mato-grossense - Beltrão, Juliane de Souza (2019)
The cultivation of chilies of the genus Capsicum is an economic activity that allows the producer a good income with small areas. The biquinho pepper (Capsicum chinense) has characteristics that distinguish it from the other peppers of the genus, mainly due to the absence of pungency (picância) in the fruits. However, further studies are needed to identify the ideal techniques for its cultivation in the Cerrado Mato-Grossense region. In this context, the objective of this study was to study the effect of nitrogen doses and irrigation slides by drip irrigation in the cultivation of biquinho pepper in Oxisol. The experiment was carried out in the field, in the experimental area of the Federal University of Mato Grosso, Rondonópolis Campus, in soil classified as dystrophic Red Oxisol. The treatments were composed of five irrigation slides [40, 60, 80, 100 and 120% of ETc demand (crop evapotranspiration)] and five nitrogen doses (0, 60, 120, 180 and 240 kg ha-1 ), having as a source the urea, totaling 25 treatments, making 100 experimental units. The liming was performed with dolomitic limestone to raise the saturation by bases to 80%. The seedlings were produced in polyethylene trays, being transplanted to the field with an average height of 7 cm, at 45 days after sowing. The planting spacing was 0.9 m between rows and 0.5 m between plants, totalizing a stand of 15 plants per experimental unit. During the vegetative development, the number of leaves, plant height, stem diameter, chlorophyll index and crown diameter were evaluated. After harvest, fruit production, fresh and dry fruit mass, number of fruits, fruit diameter and length, average fruit mass, soluble solids, water productivity and water consumption were evaluated. The data were submitted to analysis of variance and when significant, the regression analysis, at 5% significance, and response surface analysis, using software R Statistical 3.4.2®. Nitrogen fertilization showed a significant difference for plant height, number of leaves, stem and canopy diameter, chlorophyll index, fresh and dry mass of fruits, number of fruits and productivity. Irrigation blades provided a significant difference for the variables stem diameter, chlorophyll index and water productivity. The irrigation blades and nitrogen fertilization did not provide significant differences in fruit length and diameter, mean fruit mass and soluble solids content. The Irrigation blades and nitrogen doses provide gains in biquinho pepper productivity, positively influencing its development when grown on Oxisol.